Controlled trial of respiratory health worker visiting patients with chronic respiratory disability. Issue 6566 (24th January 1987) - Cockcroft, A; Bagnall, P; Heslop, A; Andersson, N; Heaton, R; Batstone, J; Allen, J; Spencer, P; Guz, A
Abstract : Seventy five patients with chronic respiratory disability were randomised to a group visited by a respiratory health worker (42) or control group (33). The first group was visited monthly by a respiratory nurse, who gave education and support. The effect of the intervention was assessed in terms of quality of life (by questionnaires), the number and duration of admissions to hospital, and the number of deaths. The questionnaires on quality of life showed no changes in either group during the study, but nearly all of the group visited by a respiratory health worker said that they valued the visits and wished them to continue. Their knowledge about their condition also improved compared with that of the controls. The duration of stay in hospital for respiratory reasons in the group visited by a respiratory health worker was longer than that of control patients. This was explained by their being scored as more ill than the controls on admission. Fewer patients died in the group visited by a respiratory health worker than in the control group (p = 0.11). The patients in the group visited by respiratory health workers may have survived longer because they sought help rather than dying at home. If confirmed this could have implications for the cost of their care.